Tradução, adaptação cultural e propriedades psicométricas da versão brasileira do Short-Form of the Mobility Assessment Tool (MAT-sf) - Oliveira, Bruna Silva (2012)
Objectives: to translate and assess the psychometric properties of the Brazilian short-form of the Mobility Assessment Tool (MAT-sf) in Brazilians community elderly. Methds: the 12 items MAT-sf went through the process of translation and back translation into Portuguese of the Brazil, considering the semantic and cultural adaptation. In a sample of 150 aged 65-74 years living in the community, the instrument's psychometric properties were evaluated by analysis of convergent and construct validity and test-retest reliability. The main outcomes measures used for validation included in the battery of tests of physical ability, self-repor measures of functional limitations, health, depression, cognitive and sex. The test-retest reliability of the instrument was assessed using the intra-class correlation coefficient (ICC), 40 subjects were reassessed after an interval of 14 days of assessment. Results: the concurrent validity for the MAT-sf was evidenced by significant correlations with SPPB (r = 0,53), number of functional limitations (r = -0,62) and depressive symptoms (r = -0,45). The construct validity of the instrument was measured by gradual and significant increase of the MAT-sf scores with high levels of physical performance and with positive self-reported health, also found that MAT-sf scores were statistically differents according to sex. The variation in MAT-sf scores (R2 = 0,41) was explained by SPPB, number of limitations for activities of daily life and depressive symptoms. High values for test-retest reliability was evidencend by ICC = 0,94, 95% CI = 0,90 0,97. Conclusions: the Brazilian version of the short-form of the Mobility Assessment Tool has values of validity and reliability to ensure its use in elderly populations living in communities